1990
DOI: 10.1093/schbul/16.4.627
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal EEG Responses to Photic Stimulation in Schizophrenic Patients

Abstract: Numerous studies have differentiated schizophrenic patients and normal controls in electroencephalography (EEG) spectral patterns recorded at rest. We replicated the resting EEG spectral differences between these groups and observed significant differences in periodic photic stimuli on the EEG spectra. Drug-free schizophrenic male patients (n = 8, mean age = 23.9) and normal male controls (n = 11, mean age = 24.3) were studied. Eighty seconds of EEG were collected from each subject for each of four experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 24 publications
2
23
0
1
Order By: Relevance
“…Although it has been reported that schizophrenic patients show a reduction in EEG photic driving responses [25][26][27] as well as abnormal VEP patterns [28,29], there have been no studies specifically investigating EEG coherence during PS in these patients. The present study showed that the schizophrenic patients had significantly higher intrahemispheric coherence than the control subjects on EEGs recorded during PS at 5 and 15 Hz.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has been reported that schizophrenic patients show a reduction in EEG photic driving responses [25][26][27] as well as abnormal VEP patterns [28,29], there have been no studies specifically investigating EEG coherence during PS in these patients. The present study showed that the schizophrenic patients had significantly higher intrahemispheric coherence than the control subjects on EEGs recorded during PS at 5 and 15 Hz.…”
Section: Discussionmentioning
confidence: 99%
“…A recent histopathological study documented abnormal neuronal density in the primary visual cortex of schizophrenic patients [24]. In addition, it has been reported that schizophrenic patients show abnormalities in EEG driving responses to PS [25][26][27] as well as in pattern-reversal visual-evoked potentials (VEPs) [28,29]. It is assumed therefore that a coherence analysis of EEGs recorded during PS would provide a useful means to assess the cerebral functioning of schizophrenic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, light stimulation is commonly used in routine EEG examinations and has proven to be useful in investigating neurological disorders (Takahashi 1989). However, numerous studies have performed only spectral analysis of the EEG induced by photic stimuli (Rice et al 1989;Jin et al 1990). Nonlinear methods may be helpful in diagnosing pathological states of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Electrophysiological measurement of photic stimulation has found reduced "photic driving" in the power spectra of patients with schizophrenia (12). It is a question for further investigation whether subjects who show reduced photic driving in the EEG also show enhanced CBF activation.…”
Section: Discussionmentioning
confidence: 99%